Circulating miRNA-19b as a biomarker of disease progression and treatment response to baricitinib in rheumatoid arthritis patients through miRNA profiling of monocytes - Ciechomska, Marzena; Roszkowski, Leszek; Burakowski, Tomasz; Massalska, Magdalena; Felis-Giemza, Anna; Roura, Adria-Jaume (Frontiers in Immunology, 2023)
Introduction A number of studies have demonstrated a key role of miRNA isolated from cells, tissue or body fluids as disease-specific biomarkers of autoimmune rheumatic diseases including rheumatoid arthritis (RA) and systemic sclerosis (SSc). Also, the expression level of miRNA is changing during disease development, therefore miRNA can be used as biomarkers monitoring RA progression and treatment response. In this study we have investigated the monocytes-specific miRNA that could serve as potential biomarkers of disease progression observed in sera and synovial fluids (SF) in early (eRA) and advanced (aRA) RA and in RA patients before and 3 months after selective JAK inhibitor (JAKi) -baricitinib treatment. Methods Samples from healthy control (HC) (n=37), RA (n=44) and SSc (n=10) patients were used. MiRNA-seq of HC, RA, and SSc monocytes was performed to find versatile miRNA present in different rheumatic diseases. Selected miRNAs were validated in body fluids in eRA (<2 years disease onset) and aRA (>2 years disease onset) and RA patients receiving baricitinib. Results Using miRNA-seq, we selected top 6 miRNA out of 95 that were significantly changed in both RA and SSc monocytes compared to HC. To identify circulating miRNA predicting RA progression, these 6 miRNA were measured in eRA and aRA sera and SF. Interestingly, miRNA (-19b-3p, -374a-5p, -3614-5p) were significantly increased in eRA sera vs HC and even further upregulated in SF vs aRA sera. In contrast, miRNA-29c-5p was significantly reduced in eRA sera vs HC and even further decreased in SF vs aRA sera. Kegg pathway analysis predicted that miRNA were involved in inflammatory-mediated pathways. ROC analysis demonstrated that miRNA-19b-3p (AUC=0.85, p=0.04) can be used as biomarker predicting JAKi response. Discussion In conclusion, we identified and validated miRNA candidates which were present simultaneously in monocytes, sera, SF and that can be used as biomarkers predicting joint inflammation and monitoring therapy response to JAKi in RA patients.